2017
DOI: 10.1002/aoc.3798
|View full text |Cite
|
Sign up to set email alerts
|

Facile synthesis of magnetic hybrid metal–organic frameworks with high adsorption capacity for methylene blue

Abstract: A magnetic hybrid material (Fe3O4‐COOH/HKUST‐1) was easily synthesized via a two‐step simple solvothermal method. Through adding sodium acrylate directly into the synthesis of Fe3O4 spheres, the surface has more carboxyl groups. It is notable that the reactions proceed without use of organic surfactants. The magnetic hybrid material was characterized using various techniques. The magnetic hybrid material has a high specific surface area (430.15 m2 g−1) and excellent magnetism (23.65 emu g−1). It is an efficien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 31 publications
(9 citation statements)
references
References 42 publications
1
8
0
Order By: Relevance
“…The process of fabrication is shown in Figure . Lin et al reported the adsorption of HKUST‐1 to MB synthesized by a hydrothermal method, whose mechanism was well deduced with the second‐order reaction, and it is similar to the research of Wang et al in kinetics features. Lin et al found the optimum range of pH is between 4 and 7, where negative HKUST‐1 was formed to absorb the cationic dye.…”
Section: Application Of the Hkust‐1 And Its Derivativessupporting
confidence: 66%
“…The process of fabrication is shown in Figure . Lin et al reported the adsorption of HKUST‐1 to MB synthesized by a hydrothermal method, whose mechanism was well deduced with the second‐order reaction, and it is similar to the research of Wang et al in kinetics features. Lin et al found the optimum range of pH is between 4 and 7, where negative HKUST‐1 was formed to absorb the cationic dye.…”
Section: Application Of the Hkust‐1 And Its Derivativessupporting
confidence: 66%
“…Dye solutions (15 ml) of various concentrations were prepared. After adjustment of test solution pH (3)(4)(5)(6)(7)(8)(9), an amount of adsorbent (0.01 g; ZnO-NPs-AC or AC) was loaded into the flask. The experiments were executed at 25°C and 4.0 min sonication time in an ultrasonic device.…”
Section: Methodsmentioning
confidence: 99%
“…Wastewaters may contain various organic contaminants and dyes may enter ecosystems through textile, cosmetic, leather, plastic, food and medicinal industries which are associated with increasing global environmental hazard . Among these, textile wastewater as a pollution source contains coloured material that greatly contributes to pollution of the water environment . Most dyes are carcinogenic, toxic in combinations and harmful, and decrease solar light penetration in aquatic media which subsequently generates harmful and hazardous problems for the environment and human health .…”
mentioning
confidence: 99%
See 2 more Smart Citations